On Lie 2-Dialgebras (Communications in Mathematical Research, 2020)
A Lie 2-bialgebra is a Lie 2-algebra equipped with a compatible Lie 2-coalgebra structure. In this paper, we give another equivalent description for Lie2-bialgebras by using the structure maps and compatibility conditions. We can usethis method to check whether a 2-term direct sum of vector spaces is a Lie 2-bialgebraeasily.